SWATShare – A web platform for collaborative research and education through online sharing, simulation and visualization of SWAT models. (January 2016) - Rajib, Mohammad Adnan; Merwade, Venkatesh; Kim, I Luk; Zhao, Lan; Song, Carol; Zhe, Shandian
Abstract: Hydrologic models for a particular watershed or a region are created for addressing a specific research or management problem, and most of the models do not get reused after the project is completed. Similarly, multiple models may exist for a particular geographic location from different researchers or organizations. To avoid the duplication of efforts, and enable model reuse and enhancement through collaborative efforts, a prototype cyberinfrastructure, called SWATShare, is developed for sharing, execution and visualization of Soil and Water Assessment Tool (SWAT). The objective of this paper is to present the software architecture, functional capabilities and implementation of SWATShare as a collaborative environment for hydrology research and education using the models published and shared in the system. Besides the capability of publishing, sharing, discovery and downloading of SWAT models, some of the functions in SWATShare such as model calibration are supported by providing access to high performance computing resources including the XSEDE and cloud. Additionally, SWATShare can create dynamic spatial and temporal plots of model outputs at different scales. SWATShare can also be used as an educational tool within a classroom setting for comparing the hydrologic processes under different geographic and climatic settings. The utility of SWATShare for collaborative research and education is demonstrated by using three case studies. Even though this paper focuses on the SWAT model, the system's architecture can be replicated for other models as well. Highlights: A cyberinfrastructure is developed for sharing and publication of hydrologic models. SWATShare is a platform for collaborative research and education using SWAT model. SWATShare can be used for online SWAT simulation, calibration and visualization. SWATShare uses publicly available distributed computing resources.